Implementasi Pembelajaran Bahasa Arab Materi Qawaid Menggunakan Media Visual Wall Chart Di Madrasah Aliyah - Nisa, Luthfiyah Khoirun; Mutholib, Abdul (Alsina : Journal of Arabic Studies, 2024)
This study aims to evaluate the implementation of Arabic language instruction on grammar material using visual media wall charts in the X grade of MA NU 03 Sunan Katong Kaliwungu Kendal during the 2023/2024 academic year, as well as to assess the suitability of this media in accordance with the SECTIONS guidelines. The research employs a qualitative descriptive method with the primary subjects being the Arabic language teacher, the principal, and 33 students from class XD. Data were collected through observations, interviews, and documentation, and analyzed using triangulation of techniques and sources. The results indicate that the implementation of learning consists of three stages: preparation, execution, and follow-up. The preparation stage involves developing learning materials and creating the wall chart. The execution stage includes introducing the wall chart, explaining categories and definitions, sentence structure, providing examples, Q&A sessions, interactive exercises, as well as discussions and presentations. The follow-up stage includes group assessments and daily quizzes. Based on the SECTIONS guidelines, the selection of the wall chart media aligns with the aspects of Student, Ease of Use, Cost, Teaching and Media Selection, Interaction, Organizational Issues, and Security and Privacy. However, it does not meet the Networking aspect, as it does not connect students with scientific communities and quality learning resources through digital media.